2005
DOI: 10.1017/s0959259806001961
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to the stability of anticoagulation control and outcome of thromboembolic prophylaxis in the older population

Abstract: 2005). Factors contributing to the stability of anticoagulation control and outcome of thromboembolic prophylaxis in the older population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…8,11,[32][33][34][35][36][37][38][39][40][41] Kagansky et al 8 showed that older patients (N = 323) with better knowledge about their warfarin therapy (measured by a warfarin knowledge-testing questionnaire) had 45% of their international normalized ratio (INR) values within the therapeutic range as compared with patients with poorer knowledge (35%; P < .001). Tang et al 34 also reported a weak but positive correlation between patients' knowledge of warfarin therapy and the number of INR values that were within the target range (P = .024).…”
Section: Importance Of Knowledge About Warfarin In Relation To Effectmentioning
confidence: 99%
“…8,11,[32][33][34][35][36][37][38][39][40][41] Kagansky et al 8 showed that older patients (N = 323) with better knowledge about their warfarin therapy (measured by a warfarin knowledge-testing questionnaire) had 45% of their international normalized ratio (INR) values within the therapeutic range as compared with patients with poorer knowledge (35%; P < .001). Tang et al 34 also reported a weak but positive correlation between patients' knowledge of warfarin therapy and the number of INR values that were within the target range (P = .024).…”
Section: Importance Of Knowledge About Warfarin In Relation To Effectmentioning
confidence: 99%